Design of resonant structures in resin matrix to mitigate the blast wave with a very wide frequency range. (16th March 2020) - Li, Q Q; He, Z C; Li, E; Liu, P; Lin, X Y; Wu, Y
Abstract: In this work, resonant structures (RSs) are embedded in the resin matrix to form the micro-scale artificial composite materials to mitigate the blast wave with a very wide frequency range (BWR). The propagation of stress waves in the resin and composite materials is described, and the composite materials exhibit stronger blast wave attenuation characteristic compared with the pure resin material. The attenuation mechanism of the composite materials is explained in detail through the absorption, storage and conversion of impact energy. In addition, the influences of materials of the RSs on the performances of the composite materials are analyzed, and the RS is redesigned to further improve the attenuation effect of the composite material. Equivalent model of the composite material is first proposed and established based on the weakly nonlinear lattice system (WNLS). At the same time, artificial tree algorithm is applied to design its spring stiffness parameters. Based on the WNLS, a three-dimensional composite material plate structure is built to mitigate the overpressure of blast wave at the macro-scale. Compared with traditional materials, the composite material exhibits superior attenuation effect and greater lightweight.